2020
DOI: 10.25259/sni_44_2020
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of neurophysiology monitoring in spine surgery: Latin America experience

Abstract: Background: Intraoperative neurophysiological monitoring (IOM) has become valuable in spine surgery. Unfortunately, it is not always available in many spine centers, especially in developing countries. Our aim was to evaluate the accessibility and barriers to IOM in spine surgery in Latin America. Methods: We designed a questionnaire to evaluate the characteristics of surgeons and their opinions on the usefulness of IOM for different spine operations. The survey was sent to 9616 members and registered user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Despite the known benefits of IONM for neurosurgical procedures in preventing iatrogenic injuries resulting in permanent and debilitating harm, cost continues to be prohibitive for its widespread adoption ( 12 , 67 ). In a survey performed in higher-middle resource countries in Latin America it was found that although 68% of the spine surgeons surveyed believed IONM was vital for complex spine surgeries, the cost barrier limited its use to only 57% of cases ( 68 ). Such data is not readily available for LIMC but one can imagine that cost is an issue as well and potentially even more limiting.…”
Section: Barriers To Ionm Utilization In Resource-limited Areasmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the known benefits of IONM for neurosurgical procedures in preventing iatrogenic injuries resulting in permanent and debilitating harm, cost continues to be prohibitive for its widespread adoption ( 12 , 67 ). In a survey performed in higher-middle resource countries in Latin America it was found that although 68% of the spine surgeons surveyed believed IONM was vital for complex spine surgeries, the cost barrier limited its use to only 57% of cases ( 68 ). Such data is not readily available for LIMC but one can imagine that cost is an issue as well and potentially even more limiting.…”
Section: Barriers To Ionm Utilization In Resource-limited Areasmentioning
confidence: 99%
“…In a survey of Latin American spine surgeons, greater than 95% of respondents said IONM was indispensable or important for pediatric and adult scoliosis correction, thoracolumbar kyphosis correction, and intradural tumors ( 68 ). Despite the overwhelming endorsement, a majority of the same surgeons readily admitted that access to IONM is limited because of lack of service availability and cost.…”
Section: Ionm Global Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In developing countries, the universal availability of the IONM is a significant limitation, especially in the emergency theatre. [6][7][8] But, the anaesthesia monitoring is routine in all cases. A visible documented change can be satisfying to the whole surgical team when there are no other ways to confirm intraoperatively.…”
Section: Descriptionmentioning
confidence: 99%